Single cell characteristics of patients with vaccine-related adverse reactions following inactivated COVID-19 vaccination - Manling Jiang; Haiqiong Yu; Li Luo; Lei Zhang; Anying Xiong; Junyi Wang; Qianhui Wang; Yao Liu; Shengbin Liu; Ying Xiong; Pingchang Yang; Christopher Chang; et al. (Taylor & Francis Group, 2023)
A good safety and immunogenicity profile was reported in Phase I and II clinical trials of inactivated SARS-CoV-2 vaccines. Here, we report two cases associated with vaccine-associated adverse events, including one patient with fever and another with anaphylactic shock resulting from inactivated SARS-CoV-2 vaccination. Cell sub-types and the importance of genetic characteristics were assessed using single-cell mRNA sequencing and machine learning. Overall, the patient with fever showed a significant increase in the numbers of cytotoxic CD8 T cells and MKI67high CD8 T cells. A potential concurrent infection with the Epstein-Barr virus enhanced interferon type I responses to vaccination against the virus. STAT1, E2F1, YBX1, and E2F7 played a key role in the transcription regulation of MKI67high CD8 T cells. In contrast, the patient with allergic shock displayed predominant increases in the numbers of S100A9high monocytes, activated CD4 T cells, and PPBPhigh megakaryocytes. The decision tree showed that LYZ and S100A8 in S100A9high monocytes contributed to the degranulation of neutrophils and activation of neutrophils involved in allergic shock. PPBP and PF4 were major contributors to platelet degranulation. These findings highlight the diversity of adverse reactions following inactivated SARS-CoV-2 vaccination and show the emerging role of cellular subtypes and central genes in vaccine-associated adverse reactions.